2015
DOI: 10.1038/ejcn.2014.279
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-specific cut-points for sarcopenia: evidence from black South African women

Abstract: The new SA cut-point had similar or greater odds of predicting reduced functional ability in older SA women when compared with other internationally accepted cut-points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
(54 reference statements)
3
14
0
Order By: Relevance
“…Only Korean population were included in this study. This cut-off values cannot be used in other races or population considering that the cutoff for sarcopenia can differ among different races [27]. However, the validity of reported prognostic factors, such as the GAP score, was confirmed in this study population, which supports the present findings.…”
Section: Discussionsupporting
confidence: 85%
“…Only Korean population were included in this study. This cut-off values cannot be used in other races or population considering that the cutoff for sarcopenia can differ among different races [27]. However, the validity of reported prognostic factors, such as the GAP score, was confirmed in this study population, which supports the present findings.…”
Section: Discussionsupporting
confidence: 85%
“…However, the FNIH aLM cut‐point had the greatest specificity and sensitivity in detecting low functional ability in ageing Gambian men and women. Our finding is consistent with a study in Black women aged 45–84 years from the north‐west of South Africa . Also, the FNIH aLM definition identified a higher prevalence of sarcopenia in Gambian women (45%) when compared with the EWGSOP definition.…”
Section: Discussionsupporting
confidence: 91%
“…Also, the FNIH aLM definition identified a higher prevalence of sarcopenia in Gambian women (45%) when compared with the EWGSOP definition. In line with our findings, there was also a greater proportion of women classified as sarcopenic (39%) from the South African study according to the FNIH aLM definition, with a higher prevalence of obesity in the Black South African women compared with Gambian women.…”
Section: Discussionsupporting
confidence: 89%
“…Different criteria include the European Working Group on Sarcopenia (EWGSOP) (30), EWGSOP2 (31), Asian Working Group for Sarcopenia (AWGS) (32), International Working Group for Sarcopenia (IWGS) (34), and the Foundation for the National Institutes of Health (FNIH) criteria (35). More locally, Kruger et al have suggested ethnic-specific cut-points for use in classifying low appendicular skeletal muscle mass index in black South African women (36). Each criterion defines sarcopenia using muscle mass and muscle function indices; however, the diagnostic cut-off values and diagnostic process differs.…”
Section: Begin With the End In Mind: Classification Of Sarcopenia And Sarcopenic Obesitymentioning
confidence: 99%